2015
DOI: 10.1021/acsami.5b05012
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Conjugated CNT-Bridged 3D Porous Graphene Oxide Membrane for Highly Efficient Disinfection of Pathogenic Bacteria and Removal of Toxic Metals from Water

Abstract: More than a billion people lack access to safe drinking water that is free from pathogenic bacteria and toxic metals. The World Health Organization estimates several million people, mostly children, die every year due to the lack of good quality water. Driven by this need, we report the development of PGLa antimicrobial peptide and glutathione conjugated carbon nanotube (CNT) bridged three-dimensional (3D) porous graphene oxide membrane, which can be used for highly efficient disinfection of Escherichia coli O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 49 publications
3
67
0
Order By: Relevance
“… 79 81 Nafion–graphene nanocomposite solution in combination with an in situ plated mercury film electrode was used as a highly sensitive electrochemical platform for the determination of Zn(II), Cd(II), Pb(II), and Cu(II) in 0.1 M acetate buffer (pH 4.6) by square-wave anodic stripping voltammetry. 82 Viraka Nellore et al 83 reported the development of PGLa antimicrobial peptide and glutathione-conjugated CNT-bridged 3DGO membrane, which can be used for removal of As(III), As(V), and Pb(II) from water. GO sheets were used in aqueous samples for a fast and efficient adsorption of Pb(II), Cd(II), Bi(III), and Sb(III) owing to its hydrophilic character and the electrostatic repulsion among the GO sheets.…”
Section: Recent Developments In Applications Of Gfnsmentioning
confidence: 99%
See 1 more Smart Citation
“… 79 81 Nafion–graphene nanocomposite solution in combination with an in situ plated mercury film electrode was used as a highly sensitive electrochemical platform for the determination of Zn(II), Cd(II), Pb(II), and Cu(II) in 0.1 M acetate buffer (pH 4.6) by square-wave anodic stripping voltammetry. 82 Viraka Nellore et al 83 reported the development of PGLa antimicrobial peptide and glutathione-conjugated CNT-bridged 3DGO membrane, which can be used for removal of As(III), As(V), and Pb(II) from water. GO sheets were used in aqueous samples for a fast and efficient adsorption of Pb(II), Cd(II), Bi(III), and Sb(III) owing to its hydrophilic character and the electrostatic repulsion among the GO sheets.…”
Section: Recent Developments In Applications Of Gfnsmentioning
confidence: 99%
“…Peptide-conjugated GO membrane has been found to be efficient in the removal and effective killing of multiple drug-resistant bacteria. 152 Similarly, Viraka Nellore et al 83 reported the development of PGLa antimicrobial peptide and glutathione-conjugated CNT-bridged 3DGO membrane, which can be used for efficient disinfection of E. coli O157:H7 bacteria. Disinfection data indicated that the PGLa- attached membrane enhances the possibility of destroying pathogenic E. coli via synergistic mechanism.…”
Section: Toxicity Of Graphene Family Nanoparticlesmentioning
confidence: 99%
“…One study however has investigated the simultaneous adsorption of heavy metals and inactivation of bacteria using a multi-component composite material of GO, CNTs and the antimicrobial peptide PGLa. Results indicated a near 100% removal of bacteria and over 95% removal of As(III) and Pb(II) [192]. The adsorption performance of the above mentioned graphene composite materials are summarized in Table 4.…”
Section: Emerging Composite Graphene Materials For Enhanced Water Purmentioning
confidence: 98%
“…PGLa is an α‐helical peptide of 21 amino acids (GMASKAGAIAGKIAKVALKAL‐NH 2 ), which can interact with bacteria's lipid membranes and destroy them. The synergistic effect of the PGLa antimicrobial peptide and GO membrane contributed to the improved disinfection activity . The wrinkled surfaces of the GO nanosheets are favorable for the immobilization of various nanomaterials, including TiO 2 ,[28b] Ag,136 Ag–CoFe 2 O 4 , and Ag 3 PO 4 .…”
Section: Synthesis Of Antimicrobic Nanomaterialsmentioning
confidence: 99%
“…B) Diagrammatic sketch of the synthesis of a CNT‐bridged 3D graphene oxide versatile membrane. Reproduced with permission . Copyright 2015, American Chemical Society.…”
Section: Synthesis Of Antimicrobic Nanomaterialsmentioning
confidence: 99%